1991
DOI: 10.1152/ajpendo.1991.260.1.e37
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of exercise and insulin action in humans

Abstract: To assess the interaction of exercise and insulin action, healthy males were studied with saline infusion (n = 5) or with a hyperinsulinemic euglycemic clamp (0.5, 1.0, 2.0, or 15.0 mU.kg-1.min-1; n = 5 at each dose) during rest (40 min), moderate-intensity cycle exercise (100 min), and recovery (100 min). Metabolism was assessed using isotopic methods and indirect calorimetry. During rest, exercise, and recovery with saline infusion, plasma glucose was unchanged, total glucose utilization (Rd) was 2.4 +/- 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
1
9

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 25 publications
5
71
1
9
Order By: Relevance
“…The average preprandial and peak therapeutic insulin concentrations in patients using a basal bolus insulin regimen are typically 120-180 and 420-480 pmol/l, respectively [5,6]. By contrast, in non-diabetic subjects, circulating insulin normally declines considerably to 30 pmol/l or less during exercise, and glucagon concentration increases in order to facilitate substrate mobilisation [7][8][9]. Depending on the exercise timing and its temporal relationship to the last insulin injection, patients with diabetes will therefore generally be carrying out exercise under markedly hyperinsulinaemic conditions, with an increased risk of hypoglycaemia [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average preprandial and peak therapeutic insulin concentrations in patients using a basal bolus insulin regimen are typically 120-180 and 420-480 pmol/l, respectively [5,6]. By contrast, in non-diabetic subjects, circulating insulin normally declines considerably to 30 pmol/l or less during exercise, and glucagon concentration increases in order to facilitate substrate mobilisation [7][8][9]. Depending on the exercise timing and its temporal relationship to the last insulin injection, patients with diabetes will therefore generally be carrying out exercise under markedly hyperinsulinaemic conditions, with an increased risk of hypoglycaemia [4].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy volunteers exercising under physiological hyperinsulinaemia [8,10], exercise and insulin interact synergistically to increase glucose uptake. In contrast, patients with type 1 diabetes exercising at 50% maximum VO 2 under basal insulin concentrations of about 60 pmol/l show reduced glucose uptake and greater reliance on fat oxidation compared with controls [11].…”
Section: Introductionmentioning
confidence: 99%
“…In experiments in non-diabetic resting humans in which a hyperinsulinaemic euglycaemic clamp was performed, the NEFA levels and fat-ox decreased, whereas CHO-ox was not influenced, indicating a shift towards a relatively higher CHO-ox. Total glucose disappearance increased in the meantime as the result of an increased glycogen deposition [24]. Leg indirect calorimetry, used to determine skeletal muscle metabolism in a similar hyperinsulinaemic euglycaemic clamp study, also revealed a suppression of fatox and an increase in CHO-ox [25].…”
Section: Discussionmentioning
confidence: 89%
“…The relative contribution of CHO-ox to EE during exercise was not only different when compared to the basal state; but also much lower than in controls. The regulatory effect of insulin on fuel oxidation during exercise was further shown in experiments in which insulin was administered to exercising humans; CHO,ox was increased compared to exercising humans not receiving insulin [29], while both non-esterified fatty acid levels and fat-ox were decreased [24]: During exercise in pancreatectomized dogs, thus in total absence of insulin, inhibition of fat-ox with methylpalmoxirate and inhibition of lipolysis with the B-blocker propranolol resulted in an increased whole body glucose uptake [30]. This means again that also during exercise, the exaggerated NEFA concentrations, caused by the absence of insulin, is a determining factor in the regulation of carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…Nutritional supplementation has been shown to optimize anabolic activity of the liver to synthesize albumin in healthy subjects, possibly owing to increases in circulating insulin, which positively modulates albumin FSR (De Feo et al, 1992). Exercise is a potential treatment for wasting syndromes as it directs more nutrients toward muscle tissues and induces a greater sensitivity and responsiveness to metabolic events regulated by insulin compared with nutrient administration alone (Wasserman et al, 1991). Although the effects of exercise on muscle protein stores have been an area of focus, its potential effects of visceral protein stores have not been studied in detail, especially in CHD patients.…”
Section: Discussionmentioning
confidence: 99%